40 PEMODELAN MERDEKA WALK TERKAIT HUBUNGANNYA DENGAN LAPANGAN MERDEKA SEBAGAI RUANG TERBUKA PUBLIK - Shandi, Yunus Boy Ari; Rahmawati, Anna Lucy; Napitupulu, Putri (Unika Santo Thomas, 2019)
It is true that Merdeka Square is accessible to everyone, can be used for various activities. In the context of behavior, space is said to be open if it allows people to act freely, can be visited and left freely and does not have the relationships needed for ownership, size, type of use, or landscape character. But City Public Open Space is not only based on that, but also there are qualitative values that must be maintained, namely access (achievement), compatibility (compatibility), views (views), identity (identity), sense (impression), and livability (convenience). This research produced a model for Merdeka Walk located in Merdeka Square, Medan.